Role of Temperature and Time Exposure for Controlled and Accelerated Synthesis of Graphene Oxide Using Tour Method - Uswatul Chasanah; Wega Trisunaryanti; Haryo Satriya Oktaviano; Triyono Triyono; Dyah Ayu Fatmawati (Indonesian Journal of Chemistry, 2022)
Synthesis of graphene oxide (GO) with the Tour method has been studied. In this procedure, phosphoric acid was mixed with sulfuric acid in the ratio of 1:9, and then potassium permanganate and graphite with the ratio of 6:1 was added in an ice bath at the variation of oxidation times of 1, 7 and 24 h and temperatures of 40, 50 and 60 °C. The GOs were characterized by UV–Visible spectroscopy, Fourier Transform InfraRed (FT-IR) spectroscopy, X-ray Diffraction (XRD), Scanning Electron Microscopy-Energy Dispersive X-Ray (SEM-EDX), and Transmission Electron Microscopy (TEM). The results show that the GO oxidized at 40 °C for 7 h (GO-7-40) has been successfully formed indicating that GO-7-40 is the most efficient GO. The GO-7-40 is characterized by a peak at 2θ = 10.89° in the XRD diffractogram, resulting calculation of the average distance between graphene layer (d) of 0.81 nm. The average number of graphene layers (n) is 4, the oxidation level (C/O) is 1.50 according to EDX data, λmax at 226 nm attributes to π→π* transitions of C=C bond in UV-Vis spectrum, and the functional groups such as O-H, C=C, C-OH, and C-OC are observed in FT-IR spectrum.